Control strategies of papaya mealybug, Paracoccus marginatus Williams & Willink infesting vegetable crops in Bangladesh (The Journal of Plant Protection Sciences, 2021)
The papaya mealybug, Paracoccus marginatus (Williams & Willink) colonize the ventral surface of the papaya leaves  along the veins and later disperse to the unripe fruits rendering them unmarketable and inedible. The damage appeared to  be in the range between 70 and 95 per cent. Generally young plants die due to heavy infestation and colony formation of  the mealybug. P. marginatus is a polyphagous pest attacking several agricultural, horticultural crops, ornamental plants  and weeds of economic value. The papaya mealybug feeds on the sap of the plants by inserting its stylets into the  epidermis of the leaf as well as into the fruit and stem. In doing so, it injects a toxic substance into the leaves. The result is  chlorosis, plant stunting, leaf deformation, early dropping of the leaves and fruits, a heavy accumulation of honeydew and  death of the host plants. Heavy infestation is capable of making fruits inedible due to the deposition of thick white waxy  material by this mealybug. Five biopesticides i.e., tobacco medicine (100 %), tobacco leaf extract (20 % ), mehgoni seed  oil (5 % ), castor seed oil (5 % ) and neem seed oil (5 % ) were used to assess their effects on the mortality of P. marginatus .  It is evident that tobacco medicine exerted the best result in terms of control followed by neem seed oil, mehgoni seed oil,  castor seed oil and tobacco leaf extract (20 % ).
Keywords: Papaya mealybug; Paracoccus marginatus; control measures; bio-pesticide use; vegetable crops,Bangladesh